Patterns of scrotal pain in a hospital setting - Chapagain, Suman; Subedi, PP; Thakur, DK; Poudel, S; Luitel, BR; Chalise, PR; Sharma, UK; Gyawali, PR; Shrestha, GK (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Scrotal pain is a common urological condition. Common causes of scrotal pain are testicular torsion, epididymitis, epididymo-orchitis and occasionally due to post vasectomy pain, varicocele, testicular trauma etc. The objective of our study is to review the different disease patterns in patients presenting with scrotal pain in a tertiary care hospital.Methods: Patients presenting with scrotal pain to the out-patient clinic and the emergency department were included in the study. All patients were subjected to urinalysis and ultrasound of scrotum with color Doppler study when needed. Descriptive variables were studied and analyzed.Results: Eighty three patients were enrolled in the study during the period of one year. Age ranged from 13 to 72 years; most of the patients were less than 40 years and more than 20 years. Among this age group non-specific orchalgia was very common. Isolated epididymitis was seen in only 4 (4.81%) patients. Epididymo-orchitis was found in 16 (19.27%) patients. Torsion of testis was found in 6 patients (7.22%). The major bulk of the patients presenting with scrotal pain were nonspecific which was found in 39 (46.98%) and exact cause could not be found in them. Total of 15 (18%) patients had acute presentation.Conclusion: Management of Scrotal pain can be simple or at times organ threatening, proper diagnosis and treatment by clinical judgment and necessary investigation is very important.Journal of Society of Surgeons of NepalVol. 17, No. 2, 2014, Page: 31-34